Avaliação de métodos de estimação de altura e de estratificação vertical em uma floresta estacional semidecidual - Curto, Rafaella de Angeli (2011)
This study aimed to evaluate methods for estimating the total height of trees and methods for vertical stratification in a native forest. This study was conducted in a fragment of 52 ha of Semideciduous Seasonal Forest, known as Rosal Forest, located in the municipality of Guaçuí-ES. For this, it was used the method of sampling a fixed area, distributing systematically a total of 16 parcels of 600 m2 in the field, totalizing a sampled area of 0.96 ha. It was performed a descriptive analysis of the trees total height and to assess the accuracy in obtaining this variable, five estimation methods were proposed: Hypsometer Vertex; digital Clinometer; estimation with aid of a 15 meters ruler; and visual estimation with and without training; in three height classes: Class 1 (15,00 to 17,99 m), Class 2 (18,00 to 20,99 m) and, Class 3 (> 21,00 m), totaling 15 treatments. To compare treatments, 211 individuals were measured, 124 in flat ground and 87 in sloping ground, and the total height of these was obtained by means of climbing. The height data were compared by t test, at a 5% probability, and also performed graphical analysis of waste and additional statistics. It was also evaluated the methods execution speed, and the factors: number of operators, cost, ruggedness, easiness of observation and compactness. For the evaluation of vertical stratification, four different methods were used, as follows: Method 1 - Souza (1990), Method 2 - Souza et al. (2003), Method 3 - IUFRO, and Method 4 - Calegário et al. (1994). In addition, the species composition, diversity, structure and horizontal diameter of the forest under study were assessed. About the methods for height estimation, the estimation method without training showed the worst performance in terms of accuracy, for both ground conditions and the best performance was observed in the estimation method with training, since the slope affected the height estimation. There was a tendency to underestimate their height as the classes were increasing, since the estimation method without training underestimated in all classes. There were differences over the mean time for estimating the height between the two methods and over the effect of the class, excluding a few exceptions. It was sampled 1596 individuals with DAP greater than or equal to 5 cm, totaling 246 species. The most representative families in numbers of species were: Fabaceae, Lauraceae, Myrtaceae and Rubiaceae. The Shannon-Weaver diversity index (H) found in the sample reaches a significant value. The most important species in the community, taking the IVI% as basis, are Mabea fistulifera, Siparuna guianensis, Pseudopiptadenia contorta, Apuleia leiocarpa and Myrcia fallax. The diameter structure of the studied forest fragment distribution has a reversed-J-shape, common in native forests. Among the vertical stratification methods, the method 1 did not allow a detailed analysis of the behavior of the species in stratum II, because of its strong tendencies to concentrate a greater number of individuals in that stratum, yet the method 2 has allowed a more detailed strata. The method 3, played down the issue found in method 1, but the change of the dominant height of the sample can change the whole discussion, showing weakness in the method. The method 4 did not bring good results for the stratification of the forest in the study, since it divided the forest in only two layers high